2010
DOI: 10.1017/s0317167100010222
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy as Gold Standard in FDG-PET Studies in Dementia

Abstract: Cognitive impairment is an area of great concern in the media and for clinicians around the world. In the past 20 years, many articles have been written about positron emission tomography (PET) imaging with F18-fluorodeoxyglucose (FDG), either to investigate its qualities as a diagnostic tool or, more recently, as inclusion criteria in clinical trials 1 . However, the routine use of FDG-PET in the investigation of dementia is not recommended in the guidelines published by the American Academy of Neurology 2 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…Abnormalities on 18 F-FDG PET and perfusion SPECT in AD are broadly similar with hypometabolism (for 18 F-FDG PET) and hypoperfusion (for SPECT) commonly affecting temporoparietal areas in a bilateral distribution, with the posterior cingulate and medial temporal areas particularly affected in AD and sensory motor cortices, including the cerebellum, largely spared (5,6). Changes in DLB overlap with the changes in AD, though more profound parietooccipital hypometabolism and hypoperfusion is seen in DLB (5,7).…”
mentioning
confidence: 78%
“…Abnormalities on 18 F-FDG PET and perfusion SPECT in AD are broadly similar with hypometabolism (for 18 F-FDG PET) and hypoperfusion (for SPECT) commonly affecting temporoparietal areas in a bilateral distribution, with the posterior cingulate and medial temporal areas particularly affected in AD and sensory motor cortices, including the cerebellum, largely spared (5,6). Changes in DLB overlap with the changes in AD, though more profound parietooccipital hypometabolism and hypoperfusion is seen in DLB (5,7).…”
mentioning
confidence: 78%
“…Autopsy studies will be useful to outline the specific neuropathological changes that underlie the cognitive and behavioral symptoms of ADHD and to determine the extent to which these changes overlap with those of known dementias (e.g., plaques and tangles, Lewy bodies, vasculopathy). In the field of dementia, such studies have been instrumental in establishing gold standards for diagnosis (Durand-Martel et al, 2010 ) and in establishing clinico-pathological (Callahan et al, 2016 ) or imaging-pathological associations (Dallaire-Théroux et al, 2017 ) that can be used to guide or corroborate diagnoses in vivo . As such, the pathological substrates of the most common dementias have been relatively well-characterized.…”
Section: Future Directionsmentioning
confidence: 99%
“…[3][4][5][6][7] It had previously been shown that quantitative EEG (qEEG) derived from rapid-eye-movement (REM) sleep was a better diagnostic tool than qEEG derived from wakefulness to discriminate mild to moderate AD subjects from age-matched healthy controls. 8,9 The regions affected by EEG slowing in REM sleep (temporal, parietal and, to a lesser degree, frontal regions) were the same that were found to have a decreased cerebral blood flow or glucose metabolism 10 (and for metaanalyses, see Durand-Martel et al 11 and Yeo et al 12 ) and a greater loss of cells (for meta-analysis, see Durand-Martel et al 11 ) in AD. Furthermore, REM sleep qEEG in mild to moderate AD subjects was correlated with the cognitive status and the interhemispheric asymmetry of cerebral blood flow assessed by single photon emission computed tomography (SPECT).…”
Section: Introductionmentioning
confidence: 97%